University, inclusive language and hate in social networks: A comparative study between Argentina and Brazil - Quargnenti, Camila; Alazraki, Laura (Comunicación y Género [Communication and Gender], 2026)
This article aims to analyze the hate reactions in social networks to the pronouncement regarding inclusive language of the Provincial University of Cordoba (Argentina) and the Universidade Federal de Santa Maria (Brazil). Three posts made by each of these universities between 2020 and 2022 were observed. A review of the publications of both universities and an analysis of their comments were carried out. The “expected” discourses around the Universities were recognized as well as the linguistic survivals that are articulated (Butler, 1997). The linguistic preconcept (Bagno, 1999) and its relationship with the LI was addressed. Finally, emotions were analyzed as constructions that shape individual and collective bodies (Ahmed, 2015).
Keywords: hate; social networks; comparative study; inclusive languag; university